OPENING ADDRESS TO ARTICLE T.Y. GOGBERASHVILI, G.A. KARKASHADZE, L.S. NAMAZOVA-BARANOVA, O.I. MASLOVA «NEUROPSYCHOLOGICAL TECHNIQUES IN PEDIATRICS: POSSIBILITIES AND PROSPECTS OF THEIR USE» - article editorial (Union of pediatricians of Russia, 2011)
.